Probiotics for broilers exposed to heat stress from 15 days of age - Ribeiro, Jéssica Carla das Dôres (2021)
The poultry sector demands alternative additives to antibiotics that can be used as performance enhancers. Therefore, an experiment was conducted to evaluate the effects of probiotics on performance, intestinal health and redox status of broilers exposed to heat stress from 15 days of age. A total of 720 Cobb-500 broilers were distributed in eight treatments (diets), evaluated in six replicates of 15 broilers, as follows: basal diet (BD) without antibiotic and probiotic (T1); BD supplemented with zinc bacitracin (T2), BD supplemented with a commercial probiotic of Bacillus subtilis DSM 17299 (T3); BD supplemented with non-commercial probiotic of Lactococcus lactis NCDO 2118, Lactobacillus delbrueckii CNRZ 327, Escherichia coli CEC 15 or Saccharomyces boulardii (T4, T5, T6 and T7, respectively), and BD supplemented with the association of the four non-commercial probiotics (T8). Feed intake (FI), weight gain (WG) and feed conversion (FC) were determined in the period from 1 to 42 days of age. Carcass and cuts yield, abdominal fat deposition, cloacal temperature, weight and length of intestine, activity of myeloperoxidase and eosinophilic peroxidase enzymes in the jejunum, jejunal histomorphometry, gene expression in the jejunum (occludin, zonulin, interleukin-8, cholecystokinin, ghrelin and heat shock protein-70) and liver (heat shock protein-70), in addition to malondialdehyde (MDA) level and superoxide dismutase (SOD) activity were measured in the intestine, liver and blood of broilers at 42 days old. Broilers fed diet T1 exhibited lower (P < 0.05) WG and live weight at slaughter, in addition to worse FC (P < 0.05). However, diets containing one or the probiotics blend resulted in better WG, FC and live weight at slaughter, similar to that observed for broilers of the T2 group. The highest (P < 0.05) cloacal temperature was determined in broilers of the T6 group. There was higher (P < 0.05) hepatic MDA concentration in the broilers of the T1 and T7 groups, and lower concentration (P < 0.05) in group T3. In blood, the MDA content was higher (P < 0.05) in the T4 group and lower (P < 0.05) in the T5 group. The T8 diet resulted in higher (P < 0.05) serum SOD activity, while diets T1 and T5 resulted in lower (P < 0.05). There was no effect (P > 0.05) of the experimental diets for the other evaluated parameters. It is concluded that broilers challenged by heat stress from 15 days of age and fed diet without antibiotic and probiotic exhibit worse performance. However, all non-commercial probiotics evaluated, supplemented alone or as a blend, were shown to be efficient in improving broiler performance in a similar magnitude to that observed when the diet contains the antibiotic zinc bacitracin or the commercial probiotic of Bacillus subtilis DSM 17299.